Ferroptosis in hematological malignant tumors - Liu, Yong; Du, Zefan; Huang, Junbin; Li, Tianwen; Zhang, Jing; Li, Yixian; Yi, Wenfang; Chen, Chun (Frontiers in Oncology, 2023)
Abstract Ferroptosis is a non-apoptotic cell death mode described in recent years. It is characterized by cellular accumulation of lipid reactive oxygen species that ultimately leads to oxidative stress and cell death. It plays a pivotal role in normal physical conditions and the occurrence and development of various diseases. Many studies have shown that tumor cells of the hematological system, such as leukemia and lymphoma, are sensitive to ferroptosis. Regulating the regulatory factors of the Ferroptosis pathway can accelerate or inhibit the disease progression of tumors. Here, we review the mechanism of Ferroptosis and its current research in hematological malignancies. Understanding the role of ferroptosis could provide valuable information regarding the treatment and prevention of these devastating diseases.